Case History of the Disastrous Debris Flows of Tianmo Watershed in Bomi County, Tibet, China： Some Mitigation Suggestions - Ge, Yong-gang; Cui, Peng; Su, Feng-huan; Zhang, Jian-qiang; Chen, Xing-zhang (Journal of mountain science, 2014)
Debris flows and landslides, extensively developing and frequently occurring along Parlung Zangbo, seriously damage the Highway from Sichuan to Tiebt（G318） at Bomi County. The disastrous debris flows of the Tianmo Watershed on Sept. 4, 2007, July 25, 2010 and Sept. 4, 2010, blocked Parlung Zangbo River and produced dammed lakes, whose outburst flow made 50 m high terrace collapse at the opposite bank due to intense scouring on the foot of the terrace. As a result, the traffic was interrupted for 16 days in 2010 because that 900 m highway base was destructed and 430 m ruined. These debris flows were initiated by the glacial melting which was induced by continuous higher temperature and the following intensive rainfall, and expanded by moraines along channels and then blocked Parlung Zangbo. At the outlet of watershed,the density, velocity and peak discharge of debris flow was 2.06 t/m3, 12.7 m/s and 3334 m3/s, respectively. When the discharge at the outlet and the deposition volume into river exceeds 2125 m3/s and 126×103 m3, respectively, debris flow will completely blocked Parlung Zangbo. Moreover,if the shear stress of river flow on the foot of terrace and the inclination angel of terrace overruns 0. 377 N/m2 and 26°, respectively, the unconsolidated terrace will be eroded by outburst flow and collapse. It was strongly recommended for mitigation that identify and evade disastrous debris flows, reduce the junction angel of channels between river and watershed, build protecting wall for highway base and keep appropriate distance between highway and the edge of unconsolidated terrace.